PENANAMAN NILAI â€“ NILAI PENDIDIKAN BERBUSANA MUSLIMAH DALAM BUKU â€œMAKIN SYARâ€™I MAKIN CANTIKâ€ KARYA AGUS ARIWIBOWO DAN FIDAYANI - irma_agust; Masruroh, Laily (Al Tadib : Jurnal Ilmu Pendidikan, 2022)
Cultivating educational values is a process or effort to impart knowledge to do something valuable so that it can have an influence on individual growth, one of which is to dress Muslim women properly according to islamic law. The objectives of this study include the first, to describe the cultivation of educational values in muslim womenâ€™s clothing, second, to describe the supporting factors for women in muslim womenâ€™s clothing, and third, to describe the onhibiting factors for women in dressing muslim women. This research includes librari research with a qualitative approach. The data collection technique in this literature research is to collect primary and secondary data sources and then the data is analyzed using descriptive methods. Based on this research, it was found that the supporting factor for women in muslim dress is because of their awareness that covering their genitals in an obligation. While one obstacle for women in dressing muslim women is that women think that wearing muslsim clothes can hinder all their activities.